Literatura, cinema, parques e produtos: Branca de Neve e suas traduções intersemióticas - Silva, Débora Cibele de Benedetto e (2014)
Approximately one hundred years after its first publication in Children s and Household Tales, by Jacob and Wilhelm Grimm, the tale Snow White is translated into a movie by the Disney Studio in 1937; Snow White and the Seven Dwarfs is the first full length animated film in the history of the movies. Due to its enormous success, Snow White and the Seven Dwarfs becomes one of the definite versions of the tale registered by the Brothers Grimm. What is more, this version influences countless other productions made after its release. Subsequently, the Disney Company devises other intersemiotic translations to the tale, some of which are attractions in Disney theme parks and various retail products sold by the Disney Store. Such an expansion characterizes Disney as an expansionist company which makes of use of a portfolio of brands and media to differentiate content in order to develop creative, innovative and profitable entertainment experiences and related products. The translations to Snow White made by the Disney Company allow the audience to interact with the characters and universe of the movie in a deeper way and, moreover, they increase the niches of consumers who may appreciate the story. An academic study about such intersemiotic translations may help us comprehend in which ways the audience, in general, interacts with fairy tales nowadays. In order to do so, the following dissertation proposes a dialogue between literature, movies and communication, and presents an analytical thinking process which starts with a literary analysis of the Grimm s tale, reflects upon the concept of intersemiotic translation and then focuses on some of the translations to Snow White devised by Disney.